Telopathes MacIsaac & Best 2013 - Lima, Manuela M.; Cordeiro, Ralf T. S.; Perez, Carlos D. (Zenodo, 2019)
Genus Telopathes MacIsaac & Best, 2013 Type-species. Telopathes magna MacIsaac & Best, in MacIsaac et al. , 2013 (by original designation). Diagnosis. “Corallum sparsely branched to the second order, branching not restricted to one plane, with branches directed distally. Stem and branches pinnulate. All pinnules simple, directed distally at an angle from the axis of the branch, in two anterolateral rows, arranged in either subopposite or alternate order. Pinnules long, maximum size estimated at up to 30 cm, the longest found on the stem and primary branches, with pinnules decreasing notably in length at branch tips. Spines are simple, conical, smooth, and compressed laterally. Polyps are elongate and arranged uniserially on branches and pinnules, and are comprised of three distinct sections separated by deep involutions. Preserved polyps range from 4.0– 7.1 mm in transverse diameter” (MacIsaac & Best, 2013). Distribution. western North Atlantic (MacIsaac & Best, 2013). Published as part of Lima, Manuela M., Cordeiro, Ralf T. S. & Perez, Carlos D., 2019, Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic, pp. 1-67 in Zootaxa 4692 (1) on page 43, DOI:10.11646/zootaxa.4692.1.1, http://zenodo.org/record/3528942